A Comparative Analysis of The Performance of Sharia-Based Stocks Versus Conventional Stocks in Manufacturing Companies Listed on The Indonesian Stock Exchange - Oktya Tri Banowati; Arifuddin Arifuddin; Wa Ode Aswati (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study investigates the performance variance between Sharia compliant and conventional equities within the Indonesian manufacturing sector from 2021 to 2025. Utilizing a quantitative comparative design and purposive sampling, a balanced matrix comprising eight Islamic stocks from the Jakarta Islamic Index and four traditional stocks from the LQ45 index was established, yielding sixty firm year data points. Financial performance was decomposed into historical closing returns and asset volatility risks, which were then evaluated through robust parametric diagnostic procedures and Independent Sample t-Tests. The empirical findings demonstrate that both asset classes exhibit statistical parity, with significance values consistently falling well above the standard alpha threshold. This structural convergence implies that the financial screening criteria governing ethical portfolios do not impose a diversification penalty or reduce capital appreciation efficiency. Instead, aggregate macroeconomic forces, monetary policy adjustments, and sectoral industrial demand exert a unifying influence that shapes corporate valuations across listing categories, reinforcing the practical integration of modern portfolio theory within Islamic wealth management frameworks.